Odpowiedź :
Odpowiedź:
b - 6x + 5 = 17 | -5
6x = 12 | :6
x = 2
c - -4x +2 = -2 | - 2
-4x = -4 | :(-4)
x = 1
d - -2x + 2 = -7 | -2
-2 x = -9 | *(-1)
2 x = 9 | : 2
x = 4,5
e - 5x - 7 = 3 | +7
5x = 10 | :5
x = 2
f - 2x + 3 = - 5 | - 3
2x = -8 | :2
x = -4
g - 7x - 12 = 3x - 2
7x - 12 - 3x = -2
4x - 12 = -2 | +12
4x = 10 | :4
x = 2,5
h - 9x - 3 = 2x +5
9x - 3 - 2x = 5
7x - 3 = 5 | +3
7 x = 8 | : 7
x = siedem ósmych
i - 4 x - 3 = 9 | +3
4x = 12 | :4
x = 3
j - 3x - 1 = 2x + 5
3x - 1 - 2x = 5
x - 1 = 5 | +1
x = 6
Szczegółowe wyjaśnienie:
.
Odpowiedź:
b.
6x+5=17
6x=17-5
6x=12 /:6
x=2
c.
-4x+2= -2
-4x=-2-2
-4x=-4 /: - 4
x=1
d.
-2x+2=-7
-2x= -7-2
-2x= - 9 /: - 2
x =9/2
x=4 i 1/2
e.
5x-7=3
5x=3+7
5x=10 /:5
x=2
f.
2x+3=-5
2x=-5-3
2x=-8 /:2
x=-4
g.
7x-12=3x-2
7x-3x=-2+12
4x=10 /;4
x=10/4
x=2 i 2/4
x=2 i 1/2
h.
9x-3=2x+5
9x-5x=5+3
4x=8 /:4
x=2
i.
4x-3=9
4x=9+3
4x=12 /:4
x=3
j.
3x-1=2x+5
3x-5x=2+1
-2x=1 / ;-2
x= - 1/2